2022
DOI: 10.3390/ijms23158347
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 3D-Printed ST2/Gelatin Methacryloyl/Polcaprolactone Scaffolds for Enhancing Bone Regeneration with Vascularization

Abstract: Growth factors were often used to improve the bioactivity of biomaterials in order to fabricate biofunctionalized bone grafts for bone defect repair. However, supraphysiological concentrations of growth factors for improving bioactivity could lead to serious side effects, such as ectopic bone formation, radiculitis, swelling of soft tissue in the neck, etc. Therefore, safely and effectively applying growth factors in bone repair biomaterials comes to be an urgent problem that needs to be addressed. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In our laboratory, we found that Wnt-activated osteocytes may affect bone formation by influencing surrounding skeletal cells through paracrine signaling, and specific data showed that Wnt-activated osteocytes promote bone formation, bone resorption [ 15 ], and stem cell proliferation. These findings have translational applications [ 21 , 31 , 32 ] and will be beneficial for BTE. We found that C91 effectively prevented the degradation of β-catenin in the cytoplasm of MLO-Y4 osteocytes and mediated β-catenin entry into the nucleus, thereby significantly increasing the expression of Wnt target genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our laboratory, we found that Wnt-activated osteocytes may affect bone formation by influencing surrounding skeletal cells through paracrine signaling, and specific data showed that Wnt-activated osteocytes promote bone formation, bone resorption [ 15 ], and stem cell proliferation. These findings have translational applications [ 21 , 31 , 32 ] and will be beneficial for BTE. We found that C91 effectively prevented the degradation of β-catenin in the cytoplasm of MLO-Y4 osteocytes and mediated β-catenin entry into the nucleus, thereby significantly increasing the expression of Wnt target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of our research, we found that the bone cell acellular matrix that was activated by Wnt signaling via gene manipulation accelerated the repair of critical-sized parietal bone defects by promoting osteoblast formation, angiogenesis, and neurogenesis [ 21 ]. Moreover, GelMA/PCL scaffolds containing ST2 cells pretreated with Wnt3a can effectively enhance the osteogenic and angiogenic activities of bone repair biomaterials in vitro and in vivo [ 32 ]. Our team has proven that this functional module has osteogenic and vascular functions, solves the problem of biological activity, and can be used as a good alternative material for bone regeneration and bone repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, several in vivo studies have reported that the use of composite biomaterials, such as HA/alginate or HA/collagen, improved, by approximately fourfold, the regenerative potential of endogenous MSC cells by increasing bone formation [357]. Similarly, other studies have reported that 3D systems functionalized with growth factors [358,359], angiogenic factors [360], miRNA [361], exosomes [362], antibiotics [363], and other compounds are considered to be an added value in promoting bone regeneration [358]. Several challenges remain related to the application of cell therapy or the use of tissue-engineered or functionalized scaffolds to promote bone regeneration in vivo.…”
Section: Bonementioning
confidence: 97%